(untitled) (Eurasian Medical Research Periodical, 2022)
Antimicrobial activity of the cell free culture supernatants (CFCS) was tested against the EPEC and EAEC . the Zones of inhibition of probiotic (Lactobacillus) against EPEC were compared among 105,106,107 concentrations. Regarding L. acidophilus, the best zone of inhibition was obtained at 106 concentration. L. plantarum , the best zone of inhibition was obtained at 107 concentration. While the best inhibition zone of L. rhamnosus was obtained at 106 concentration and the Zones of inhibition of probiotic (Lactobacillus) against EAEC was compared among 105 , 106 and 107 concentrations. Regarding L. acidophilus, the best zone of inhibition was obtained at 107 concentration. In case of L. plantarum, the best zone of inhibition was obtained at 106 concentration. The best zone of inhibition was obtained at the concentration 106 L. rhamnosus. The Characterization of antimicrobial substances produced by Lactobacillus has been studded The result showed the bacteriocin only has inhibitory effect against